2014
DOI: 10.1523/jneurosci.4227-13.2014
|View full text |Cite|
|
Sign up to set email alerts
|

Precuneus Is a Functional Core of the Default-Mode Network

Abstract: Efforts to understand the functional architecture of the brain have consistently identified multiple overlapping large-scale neural networks that are observable across multiple states. Despite the ubiquity of these networks, it remains unclear how regions within these large-scale neural networks interact to orchestrate behavior. Here, we collected functional magnetic resonance imaging data from 188 human subjects who engaged in three cognitive tasks and a resting-state scan. Using multiple tasks and a large sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
515
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(586 citation statements)
references
References 72 publications
(10 reference statements)
38
515
2
3
Order By: Relevance
“…In fact, lesions within the anterior cingulate cortex trigger an inability to detect errors, severe difficulty in resolving stimulus conflict, emotional instability, inattention, and even akinetic mutism, all of which may be completely or partly related to the default mode network. 10,71 As in our findings, the course of the SLF I has been previously defined by neuroimaging studies as running predominantly from the precuneus (medial BA 7) and less from the superior parietal lobule (BA 7) to the superior frontal gyrus (BA 8 and 9), SMA (BA 6), and anterior cingulate cortex by passing deep to the postcentral (BA 5) and precentral gyri (BA 4). 41,53,61,65 In our study, during medial-to-lateral and lateral-to-medial fiber dissection, the SLF I was found to be the long association fiber tract located medial to the callosal fibers and above the cingulum in the superior bank of the cingulate sulcus.…”
Section: Segmentation Of the Superior Longitudinal Fasciculussupporting
confidence: 78%
See 1 more Smart Citation
“…In fact, lesions within the anterior cingulate cortex trigger an inability to detect errors, severe difficulty in resolving stimulus conflict, emotional instability, inattention, and even akinetic mutism, all of which may be completely or partly related to the default mode network. 10,71 As in our findings, the course of the SLF I has been previously defined by neuroimaging studies as running predominantly from the precuneus (medial BA 7) and less from the superior parietal lobule (BA 7) to the superior frontal gyrus (BA 8 and 9), SMA (BA 6), and anterior cingulate cortex by passing deep to the postcentral (BA 5) and precentral gyri (BA 4). 41,53,61,65 In our study, during medial-to-lateral and lateral-to-medial fiber dissection, the SLF I was found to be the long association fiber tract located medial to the callosal fibers and above the cingulum in the superior bank of the cingulate sulcus.…”
Section: Segmentation Of the Superior Longitudinal Fasciculussupporting
confidence: 78%
“…41,53,61 The default mode network is the region of the brain that becomes activated when the brain is resting (but alert) and attention is focused on internal tasks such as memory retrieval and self-reflection. 71 We suggest that the main subcortical connection of the default mode network, the long association bundle (SLF I) connected to the precuneus, may be to the anterior cingulate region. The precuneus plays a core role in self-consciousness with regard to the default mode network, which is activated during the "resting consciousness" state in which one does not engage intentionally in sensory or motor activity.…”
Section: Segmentation Of the Superior Longitudinal Fasciculusmentioning
confidence: 88%
“…13,35,36 On the other hand, Naqvi and colleagues 37 found that smokers with brain damage involving the insula were more likely to quit smoking. The precuneus and dmPFC are key regions of the DMN 38,39 that have been found to be impaired in heroin users. 3,39,40 The precuneus is involved mainly in processing self-reflection and self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The DMN is characterized by high activity when the mind is not engaged in specific behavioral tasks and low activity during focused attention on the external environment, and the precuneus is its posterior component (22). The precuneus comprises the functional core of the DMN and plays an important role in regulating complex cognition and behavior (23)(24)(25). The functional connectivity in the DMN, including the precuneus, decreases in cognitively normal patients with type 2 diabetes, and the magnitude of the reduced connectivity is associated with insulin resistance (26).…”
Section: Discussionmentioning
confidence: 99%